A diffuse-interface model of anisotropic interface thermal conductivity and its application in thermal homogenization of composites. (15th April 2022) - Yang, Yangyiwei; Fathidoost, Mozhdeh; Oyedeji, Timileyin David; Bondi, Prasanth; Zhou, Xiandong; Egger, Herbert; Xu, Bai-Xiang
Graphical abstract: Abstract: In this work, we present a diffuse-interface model of anisotropic interface thermal conductivity considering the interface thermal resistance and conductance. It allows to perform simulations with interface thermal imperfections while circumventing the technical and numerical difficulties of reconstructing complex sharp-interface microstructure. The model is implemented in a finite element method. Numerical results show good agreement with the theoretical benchmarks for both thermal conduction simulation and thermal homogenization. To further demonstrate the feasibility of the model, complex microstructures from digitized characterizations and phase-field simulations are homogenized, taking Si-Hf-N as the material system. Normalized interface thermal resistance ranging from 1 to 10 8 show prominent influence to the homogenized thermal conductivity, which converges when the thermal resistance approaches zero or infinity. Increasing thermal resistance is also unveiled to enhance the thermal anisotropy of the microstructure with highly-oriented inclusions.